Estrutura e dinâmica do fitoplânctone bacterioplâncton em cultivos de camarão no Rio Grande do Norte-Brasil: impacto sobre o ambiente natural - Santos, Margarida de Lourdes Melo Nelson dos (2008)
This work aimed to study the structure and dynamic of Phytoplankton and Bacterioplankton in a complete cycle of shrimp cultivation (Litopenaeus vannamei) and determine the environmental factors responsible for the structural changes of these communities. The study was realized in a saltwater shrimp farm (Macaíba, RN), between September/2005 and February/2006, and in a freshwater shrimp farm (Ceará Mirim, RN), between May/2007 and September 2007. The samplings were collected weekly in saltwater farm and every fifteen days in freshwater farm. Total phosphorus, chlorophyll a and environmental parameters (pH, dissolved oxygen, salinity, temperature, depth and water transparency) were measured. Qualitative and quantitative analysis of the phytoplankton and bacterioplankton were carried out. The Shannon-Wiener ecologic indexes of diversity and the Pielou equitability indexes were calculated to the phytoplankton. Bacterial density was determined by epifluorescence microscopy. The data were statistically analyzed by Pearson correlation and t-Test. Chlorophycea were predominat in salt water and in the captation/drainage point (24 to 99%). Diatoms had higher wealth. The species Choricystis minor had the highest occurrence (100%) and dominance (90-100%), thus showing its adaptation to the high temperatures, salinity and low water transparency conditions. Filamentous Cyanobacteria like Oscillatoria sp., Pseudoanabaena sp. and Phormidium sp. had constant levels. The negative correlation between chlorophycea and water transparency, and the positive correlation between chlorophyll a and salinity, showed that the phytoplankton was well adapted to the low transparency and to the high salinity. The bacterioplankton was negatively correlated with the total phosphorus and salinity. In freshwater, Cyanobacteria were predominant (>80%), presenting some producers of toxins species like Microcystis sp., Aphanizomenon sp., Cylindrospermopsis raciborskii e Anabaena circinalis. Cyanobacterial density and total phosphorus and chlorophyll a concentrations exceeded the maximum value allowed by legislation. The means of total phosphorus varied from 264 to 627 Wg.L-1 and the means of chlorophyll a oscillated between 22 and 182 Wg.L-1. The phytoplankton species were selected by low availability of the light, high pH, temperature and high availability of total phosphorus. The bacterioplankton showed high densities (5,13 x 107 to 8,50 x107 Bac.mL-1). The studied environments (ponds and rivers) presented a high level of trophic state based on the high concentrations of chlorophyll a and total phosphorus and cyanobacteria dominance. The composition of species in the ponds and rivers was similar, as well as high concentrations of total phosphorus and chlorophyll a, highlighting the pollution caused by the discharges of the farms in natural environment